EQUIPMENT FOR THE REMOTE AND CENTRALIZED CONTROL FROM MOBILE ANDROID PHONE TO THE DIFFERENT APPLIANCE EXISTENT IN THE HOUSEHOLD - Lazo Tamayo, Daniel Alejandro; Montejo Valdez, Pablo (Telemática, 2020)
In this article, an electronic design is described to centralize the control of home appliances, remotely and simply. Three types of modules are made that cover the control of all the appliances as a whole. Each module connects independently with an application for the Android operating system via Bluetooth. One of the modules employs infrared face communicating with the equipment in the house that employs remote controls. The other two modules are used to control devices that represent inductive loads such as fans, washing machines and hydraulic pumps, and resistive loads such as loops. Besides, sensors are used and to complete the automation of household appliances. The proposed design is a tool for the centralization of the main functions of the home. Its flexibility allows it to be used in any home and its economic price favors its implementation.